2017
DOI: 10.26522/brocked.v26i2.609
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Native and Non-Native EFL Teachers’ Oral Corrective Feedback Practices: An Observational Study

Abstract: Commonly defined as L2 teachers' responses to learners' erroneous utterances, oral corrective feedback (OCF) is an interactional classroom phenomenon which frequently occurs in foreign language classes and has gained growing momentum in SLA research in recent years. However, how OCF preferences of English teachers vary in terms of their native-nonnative speaker status remains as an uncharted territory of inquiry specifically in an expanding-circle context. This study aims to reveal the differences between in-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…al., 2016;Ozmen & Aydin, 2015). Demir and Ozmen (2017) explored the oral corrective feedback practices of EFL teachers including both native and non-native. Findings of the observation indicated English speaking teachers whether native or non-native had dissimilar oral corrective feedback practices in EFL classrooms in terms of favored oral corrective feedback types, the quantity of oral corrective feedback and types of errors.…”
Section: Past Studiesmentioning
confidence: 99%
“…al., 2016;Ozmen & Aydin, 2015). Demir and Ozmen (2017) explored the oral corrective feedback practices of EFL teachers including both native and non-native. Findings of the observation indicated English speaking teachers whether native or non-native had dissimilar oral corrective feedback practices in EFL classrooms in terms of favored oral corrective feedback types, the quantity of oral corrective feedback and types of errors.…”
Section: Past Studiesmentioning
confidence: 99%
“…Feedback provides students with insights into their errors and on how to improve the expression and clarity of ideas (Starfield, 2019). While the advancement of technology has brought about innovative feedback modalities such as audio or video (Munshi & Deneen, 2018;Payne et al, 2022), there are inherent challenges in ensuring their efficacy and succinctness, especially when the feedback providers are NESB teaching staff (Bal-Gezegin, 2015;Demir & Özmen, 2017). Notably, NESB educators may often grapple in providing feedback with language and sentence structure (Starfield, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The provision of explicit CF can measure the learning progress which can be marked beyond the fewer error corrections given to the students. Another study conducted by Demir & Özmen (2017) who explore the CF preferences of native and nonnative English teachers in Turkey. The finding indicated that recast was more favorable than other types of CF.…”
Section: Introductionmentioning
confidence: 99%